Economic Perspective of Improving Energy Management and Supporting The Achievement of SDG 7: Affordable and Clean Energy - Puspita Nurlilasari (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
The oil and gas industry has long been a significant contributor to global greenhouse gas emissions, with flaring and methane emissions from production processes being major concerns. However, in recent years, there has been increasing pressure from governments, environmental organizations, and stakeholders to reduce or eliminate flaring, while capturing and storing carbon dioxide (CO₂) emissions. This article reviews recent technological advancements, strategies, and efforts undertaken by global oil and gas companies to achieve zero flaring and implement effective carbon capture and storage (CCS) solutions. Despite progress, challenges related to scale, cost, and infrastructure development remain significant barriers to the large-scale implementation of these technologies. This review highlights key case studies, technological innovations, and policy frameworks driving these efforts, while offering a future perspective on achieving a carbon-neutral oil and gas sector from an economic viewpoint.